MIR155HG suppresses the osteogenic differentiation of bone marrow mesenchymal stem cells through regulating miR-155-5p and DKK1 expression - Weimin Li; Cheng Yang; Jiamu Xu; Dongcheng Ran; Chunqing Wang (Journal of Orthopaedic Surgery and Research)
Abstract Background Increasing evidence has demonstrated that non-coding RNAs, including the lncRNA MIR155HG, are involved in the pathogenesis of postmenopausal osteoporosis (PMOP). In the current study, we studied MIR155HG function in regulation of osteogenic differentiation and tried to reveal the underlying mechanisms. Methods Forty blood samples taken from 20 PMOP patients (PMOP group) and 20 postmenopausal individuals without osteoporosis (control group) were used to compare the contents of MIR155HG and miR-155-5p via RT-PCR. Alizarin red S staining and ALP staining were used to evaluate the osteogenic differentiation potential of bone marrow mesenchymal stem cells (BMSCs). Results Elevated levels of MIR155HG and miR-155-5p were observed in the blood samples of the PMOP group. Upregulation of MIR155HG resulted in decreased expression of OPN, OSX, ALP, RUNX2 and β-catenin but increased DKK1 expression, together with decreased Alizarin red S + and ALP + staining areas. However, downregulation of DKK1 did not obviously change the above indices induced by MIR155HG upregulation. Further experiments revealed that MIR155HG caused an increase in the expression of miR-155-5p, which also serves as an inhibitor of the osteogenic differentiation of BMSCs through binding to β-catenin. Consistent with DKK1 knockdown, downregulation of miR-155-5p only also did not obviously reverse the repressive effect of MIR155HG on osteoblastic differentiation, but downregulation of DKK1 and miR-155-5p synchronously restored the osteogenic differentiation ability of BMSCs suppressed by MIR155HG overexpression. Conclusion MIR155HG suppressed the osteoblastic differentiation of BMSCs by regulating miR-155-5p and DKK1 expression. Either inhibition of miR-155-5p and DKK1 or direct suppression of MIR155HG may be effective approaches for treating PMOP.